2020
DOI: 10.1152/ajpheart.00549.2019
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related cardiovascular diseases: the search for a unifying hypothesis

Abstract: Although the extensive rollout of antiretroviral (ARV) therapy resulted in a longer life expectancy for people living with human immunodeficiency virus (PLHIV), such individuals display a relatively increased occurrence of cardiovascular diseases (CVD). This health challenge stimulated significant research interests in the field, leading to an improved understanding of both lifestyle-related risk factors and the underlying mechanisms of CVD onset in PLHIV. However, despite such progress, the precise role of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 209 publications
(266 reference statements)
0
22
0
2
Order By: Relevance
“…Despite the immense benefits that antiretroviral therapy (ART) use has brought to people living with HIV/AIDS (PLWHA), there are some associated increased risks of dyslipidemia, hyperglycemia/diabetes, gastrointestinal symptoms, obesity, and hypertension, which contribute to a higher cardiometabolic risk in this population [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Other risk factors also corroborate for cardiometabolic diseases in PLWHA, such as smoking, excessive alcohol consumption, and physical inactivity [ 1 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the immense benefits that antiretroviral therapy (ART) use has brought to people living with HIV/AIDS (PLWHA), there are some associated increased risks of dyslipidemia, hyperglycemia/diabetes, gastrointestinal symptoms, obesity, and hypertension, which contribute to a higher cardiometabolic risk in this population [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Other risk factors also corroborate for cardiometabolic diseases in PLWHA, such as smoking, excessive alcohol consumption, and physical inactivity [ 1 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some HIV-positive individuals exhibit persistent immune activation, immune failure and the development of chronic co-morbidities such as CVD (Dominick et al 2020). However, the exact role of Treg cells in this context remains unclear as they can trigger beneficial or detrimental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiple studies have reported an increased prevalence of traditional cardiovascular risk factors, such as diabetes, HTN, and smoking among HIV‐infected individuals compared to the general population 32‐35 . In addition to the traditional CVD risk factors, chronic systemic inflammation from viral infection contributes to endothelial dysfunction, immune activation, and vascular injury which further precipitates premature atherosclerosis in HIV‐infected individuals 36‐40 . HIV infection is associated with almost 50% increased risk of acute myocardial infarction as compared to the general population, even after adjustment for Framingham risk score, substance abuse, and comorbidities 41 .…”
Section: Structural Heart Disease/accelerated Atherosclerosismentioning
confidence: 99%